The role of respiratory droplet physicochemistry in limiting and promoting the airborne transmission of human coronaviruses: A critical review() - Niazi, Sadegh (Environ Pollut, 2021)
Whether virulent human pathogenic coronaviruses (SARS-CoV, MERS-CoV, SARS-CoV-2) are effectively transmitted by aerosols remains contentious. Transmission modes of the novel coronavirus have become a hot topic of research with the importance of airborne transmission controversial due to the many factors that can influence virus transmission. Airborne transmission is an accepted potential route for the spread of some viral infections (measles, chickenpox); however, aerosol features and infectious inoculum vary from one respiratory virus to another. Infectious virus-laden aerosols can be produced by natural human respiratory activities, and their features are vital determinants for virus carriage and transmission. Physicochemical characteristics of infectious respiratory aerosols can influence the efficiency of virus transmission by droplets. This critical review identifies studies reporting instances of infected patients producing airborne human pathogenic coronaviruses, and evidence for the role of physical/chemical characteristics of human-generated droplets in altering embedded viruses’ viability. We also review studies evaluating these viruses in the air, field studies and available evidence about seasonality patterns. Ultimately the literature suggests that a proportion of virulent human coronaviruses can plausibly be transmitted via the air, even though this might vary in different conditions. Evidence exists for respirable-sized airborne droplet nuclei containing viral RNA, although this does not necessarily imply that the virus is transmittable, capable of replicating in a recipient host, or that inoculum is sufficient to initiate infection. However, evidence suggests that coronaviruses can survive in simulated droplet nuclei for a significant time (>24 h). Nevertheless, laboratory nebulized virus-laden aerosols might not accurately model the complexity of human carrier aerosols in studying airborne viral transport. In summary, there is disagreement on whether wild coronaviruses can be transmitted via an airborne path and display seasonal patterns. Further studies are therefore required to provide supporting evidence for the role of airborne transmission and assumed mechanisms underlying seasonality.